Penerapan Analisis Deret Waktu Arima dalam meramalkan Wisatawan Mancanegara Asal Malaysia Tahun 2024 - 10060117091, Rido Julistio; Ilham Faishal Mahdy, S.Stat.,M.Stat (Bandung Conference Series: Statistics, 2025)
Abstract. Forecasting is an activity aimed at predicting future events, covering short-term, medium-term, and long-term periods using time series data. Time series data refers to a collection of data arranged continuously over a specific period. Forecasting techniques in time series data analysis involve statistical modeling methods, including exponential smoothing, moving average, regression, and autoregressive integrated moving average (ARIMA). The ARIMA model is categorized into three groups: autoregressive (AR), moving average (MA), and the combined ARMA (autoregressive moving average) model, which incorporates characteristics of the first two models. Stationarity checks on data can be conducted using time series plots, the Augmented Dickey-Fuller (ADF) test, and the autocorrelation function (ACF) test. The Box-Cox transformation is applied when time series data exhibit non-stationarity in variance, requiring an assessment of stationarity issues through the ADF test and ACF test. Differencing is performed after the data achieve stationarity in variance. If the data remain non-stationary in the mean, further differencing is applied. International tourists are defined as individuals traveling to a country outside their place of residence. Using the Akaike Information Criterion (AIC) test, the best-fitting model was determined to be ARIMA (1,2,1) based on the smallest AIC value. This study concludes that the ARIMA time series analysis can be utilized to forecast the number of Malaysian international tourists in 2024. Abstrak. Peramalan adalah kegiatan untuk memprediksi kejadian yang akan datang yang meliputi jangka pendek, menengah dan panjang menggunakan data deret waktu. Data deret waktu merupakan kumpulan data yang disusun pada waktu tertentu secara terus menerus. Teknik peramalan analisis data deret waktu dengan model peramalan berdasarkan pemodelan statistik yaitu (exponential smoothing, moving average, regresi dan autoregressive integrated moving average (ARIMA)). Model ARIMA dibagi ke dalam 3 kelompok, yaitu: model autoregressive (AR), moving average (MA), dan model campuran ARMA (autoregresive moving average) yang mempunyai karakteristik dari dua model pertama. Pengecekan staioner data bisa dilakukan dengan plot time series, uji ADF dan uji ACF. Transformasi Box Cox digunakan ketika data deret waktunya mengandung masalah adanya ketidakstasioneran data dalam varians, sehiggga harus ada proses pemeriksaan masalah kestasioneran yang dapat diperiksa menggunakan statistik ADF dan uji ACF. Proses pembedaan (differencing) dilakukan setelah data stasioner dalam varians. Proses pembedaan dilakukan jika data tidak stasioner dalam rata- rata. wisatawan secara internasional yakni setiap orang yang mengunjungi suatu negara di luar tempat tinggalnya. Dengan menggunakan Uji AIC dengan nilai terkecil didapatkan model terbaik ARIMA (1, 2, 1). Berdasarkan penelitian ini diketahui bahwa Analisis Deret Waktu ARIMA dapat digunakan untuk melakukan peramalan jumlah wisatawan mancanegara asal Malaysia tahun 2024.